The Behavioral Drivers of PayLater (BNPL) Use Intention: Financial FoMO, Cashless Pain of Paying, and Present Bias among Gen Z University Students in Semarang City - Affroni, Moh Zaenal; Faza Rusyda; Robetmi Jumpakita Pinem (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of Financial FoMO, Cashless Painlessness, and Present Bias on Buy Now Pay Later (BNPL) use intention among Generation Z university students in Semarang City. Using a quantitative survey of 150 BNPL users, data were analyzed with multiple linear regression in SPSS. The findings reveal that all three variables positively and significantly influence BNPL use intention, both individually and jointly. Cashless Painlessness emerges as the strongest predictor, indicating that less salient payment experiences increase intention. The model explains 65.3% of the variance in BNPL use intention (R² = 0.653).